2017
DOI: 10.1159/000464435
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Modulates DNA Methylation and Downregulates DNMT3B in Bladder Cancer

Abstract: Background: Genomic DNA methylation plays an important role in both the occurrence and development of bladder cancer. Kaempferol (Kae), a natural flavonoid that is present in many fruits and vegetables, exhibits potent anti-cancer effects in bladder cancer. Similar to other flavonoids, Kae possesses a flavan nucleus in its structure. This structure was reported to inhibit DNA methylation by suppressing DNA methyltransferases (DNMTs). However, whether Kae can inhibit DNA methylation remains unclear. Methods: Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…Chemoresistance, which leads to the failure of chemotherapy, is very common in the therapeutic process [8, 45, 46]. Thus, the development of effective chemotherapies is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoresistance, which leads to the failure of chemotherapy, is very common in the therapeutic process [8, 45, 46]. Thus, the development of effective chemotherapies is critical.…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypermethylation is associated with hypoxia and reduces the activity of oxygen-dependent ten-eleven translocation enzymes [6]. Cancer cells from many different human tumours exhibit changes in DNA methylation involving both global hypomethylation and local hypermethylation of CpG-rich gene promoters [7, 8]. Hypermethylation of promoter CpG islands implies an important mutation-independent mechanism for inactivation of tumour suppressor genes by gene silencing in cancer cells [9], which ultimately contributes to oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al (2017) demonstrated that treatment with the flavonoid kaempferol did not vary the content of 5-methylcytosine, a biomarker for global DNA methylation, in a bladder cancer xenografts model, but modulated DNA methylation in specific positions. Qiu et al (2017) demonstrated that treatment with the flavonoid kaempferol did not vary the content of 5-methylcytosine, a biomarker for global DNA methylation, in a bladder cancer xenografts model, but modulated DNA methylation in specific positions.…”
Section: Discussionmentioning
confidence: 95%
“…Although there was no change in global methylation levels in wild type TP53 cells, there was DNMT1 downregulation (2.27-and 3.57-fold downregulation for 100 and 150 μM, , which may be contributing to demethylation of tumor suppressor genes. Qiu et al (2017) demonstrated that treatment with the flavonoid kaempferol did not vary the content of 5-methylcytosine, a biomarker for global DNA methylation, in a bladder cancer xenografts model, but modulated DNA methylation in specific positions.…”
Section: Discussionmentioning
confidence: 95%
“…In this respect, kaempferol, as a chemopreventive agent, has been found to modulate DNA methylation, to suppress the protein levels of DNA methyltransferases (DNMT3B) and to induce 103 differential DNA methylation positions (dDMPs) associated with genes 50 hypermethylated and 53 hypomethylated. Additionally, it induces a premature degradation of DNMT3B by suppressing the protein synthesis with cycloheximide (CHXv) (Qiu et al, ). In a recent investigation, Kashafi and coworkers reported that kaempferol (12–100 μM) induces apoptosis and cell death in HeLa cervical cancer cells in a dose‐dependent fashion.…”
Section: Health Perspectivesmentioning
confidence: 99%